2020
DOI: 10.1038/s41598-020-66701-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Inverse Hall-Petch Behavior and Low Friction and Wear in High Entropy Alloys

Abstract: We present evidence of inverse Hall-petch behavior for a single-phase high entropy alloy (cocrfeMnni) in ultra-high vacuum and show that it is associated with low friction coefficients (~0.3). Grain size measurements by STEM validate a recently proposed dynamic amorphization model that accurately predicts grain size-dependent shear strength in the inverse Hall-Petch regime. Wear rates in the initially soft (coarse grained) material were shown to be remarkably low (~10-6 mm 3 /n-m), the lowest for any HEA teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Nevertheless, on the basis of various experiments and procedures, such as CALPHAD [ 1 , 2 , 3 ], it has been possible to identify and investigate promising systems for different applications. The fields of application range from high-temperature or cryogenic materials to corrosion-resistant and wear-resistant materials [ 4 , 5 , 6 , 7 ]. In addition to the single-phase high entropy alloys, other alloys have been developed which form precipitates in order to further influence the properties of these alloys [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, on the basis of various experiments and procedures, such as CALPHAD [ 1 , 2 , 3 ], it has been possible to identify and investigate promising systems for different applications. The fields of application range from high-temperature or cryogenic materials to corrosion-resistant and wear-resistant materials [ 4 , 5 , 6 , 7 ]. In addition to the single-phase high entropy alloys, other alloys have been developed which form precipitates in order to further influence the properties of these alloys [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other sophisticated routes exist for imparting higher strength to metals, and providing thermal stability to the underlying microstructural features, like grain boundaries and dislocations. Some relatively recent examples include the formation of thick boundaries (sometimes called complexions) [253][254][255], solution strengthening [46,81] in high entropy alloys [256][257][258][259][260][261][262][263] (where combinations of multiple elements increases the energy required for dislocation motion), and metastable amorphous bulk metallic glasses [264][265][266][267].…”
Section: Routes For Promoting Grain Boundary Sliding In Metalsmentioning
confidence: 99%
“…The wear rates were measured to be 3.64 × 10 −6 and 1.42 × 10 −6 mm 3 •N −1 •m −1 for Nb content of x = 0 and x = 2, respectively. Jones et al [358] reported that CoCrFeNiMn showed a remarkably low wear rate of 10 −6 mm 3 •N −1 •m −1 with the hardness of 1.6 GPa. Zhu et al [359] added V and Nb in equiatomic ratio into the CoCrFeNiMn (FCC phase) coating and studied the wear resistance.…”
Section: Content Variationmentioning
confidence: 99%